PENGARUH PENDAPATAN ASLI DESA (PADES), DANA DESA (DD), DAN ALOKASI DANA DESA (ADD) TERHADAP BELANJA DESA PADA 10 KECAMATAN DI KABUPATEN LEBAK - Nurpadilah; Usep Siswadi; Firmansyah (The Asia Pacific Journal Of Management Studies, 2023)
Village expenditures are expenditures from village accounts that are used to fund village implementation with the aim of meeting development needs as agreed in village deliberations and according to the Regency/City Government, Provincial Government, and Central Government. This study aims to examine and analyze the effect of Village Original Income (PADes), Village Funds (DD), Allocation of Village Funds (ADD) to Village Expenditures in 10 Districts in Lebak Regency for the 2021 Period. The method used in this study is the quantitative method. The sample of this research is 40 villages that have Village Original Income (PADes), Village Funds (DD), Village Fund Allocation (ADD) and Village Expenditures in 10 Districts in Lebak Regency for the 2021 Period. And using purposive sampling technique.. The result showed that there was no effect of Village Origional Income (PADes) on Village Expenditures partially, while the Village Fund (DD) and Village Fund Allocation (ADD) variabels partially affected Village Expenditures. The F test has a significant effect between Village Origional Income (PADes), Village Funds (DD), and Village Fund Allocation (ADD) on Village Expenditures simultaneously.